Joint Sub-Committee of the T.U.C., the Labour Party and the Co-operative Congress on the Government White Paper "A National Health Service" (minutes) - Labour Party (Great Britain) ; Co-operative Congress
1944-09-05 1944 1940s 6 pages -5- be such as to relieve the hospital from the necessity of raising substantial funds of their own. We think it would have been better, boldly to incorporate the voluntary institutions in one unified hospital system and that the failure to do so is a distinct flaw in the plan. Despite this, however, we are of opinion that the plan ought to be accepted in present circumstances. We think that the hospital service should be planned over natural hospital regions, the boundaries of which should not necessarily be co-terminus with the boundaries of existing local authorities. We support the expression of view in the Government White Paper that "despite the difficulties, the mental health service should be taken over by the new joint authority" and that hospitals for infectious diseases should also be taken over. 10. ADMINISTRATION It is noted that whilst the national health service will be the central responsibility of the Minister of Health and the Secretary of State for Scotland, they will have at their disposal a Central Medical Board which will be mainly a medical body and that this Board will employ the doctors and arrange contracts of different types with them. In addition there will be a Statutory Central Health Services Council to advise the Minister on a wide range of subjects and this would be a mixed body of technical experts bearing on health questions. Whilst we appreciate the reasons for a Central Medical Board for doctors only, we think that similar arrangements should be made for other workers. The high standard of medical service aimed at must necessarily include a high standard of training, remuneration and organisation for nursing, home visiting, ambulance, dentistry, pharmacy, ophthalmology and other sections of the health service. Just as in the case of doctors, there should be full consultation 292/847/2/10